ANALISIS AKRUAL TOTAL PADA KECEPATAN EARNINGS ADJUSTMENT : SEBELUM DAN SELAMA KRISIS MONETER - YAVIDA NURIM (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2005)
This study aims to measure the speed of earnings adjustment of public companies before and during crisis. Different economic condition implies the different level of stress. Because crisis affects the level of stress, firms involve in larger effort to improve their performance. This study predicts that companies use accruals in improving their performance. Based on examination of seven characteristic industries, the results show that before crisis all industries (except automotive industry have negative speed of adjustment) have speed of adjustment between zero and one, but during crisis only four industries have same of speed (three remaining have speed over one). The results show a significant difference speed of adjustment before and during crisis. The use of total accruals influences the changes of the speed of earnings adjustment. However, it is not caused by earnings management since abnormal accruals do not influence the changes.